2003
DOI: 10.1016/s0960-9822(03)00338-5
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Proteasome System Acutely Regulates Presynaptic Protein Turnover and Synaptic Efficacy

Abstract: Taken together, these studies demonstrate that the UPS functions locally within synaptic boutons to acutely control levels of presynaptic protein and that the rate of UPS-dependent protein degradation is a primary determinant of neurotransmission strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(207 citation statements)
references
References 60 publications
7
200
0
Order By: Relevance
“…Other studies also observed decreases in mitochondrial related genes in pyramidal neurons in the DLPFC of schizophrenia subjects (39, 40). Metabolic systems are strongly linked to the control of synaptic protein connectivity, signaling, and turnover (41-45). Thus, decreases in mitochondrial function coupled with abnormal glucose utilization in neurons could reduce the capacity of pyramidal cells to sustain a normal complement of dendritic spines, contributing to the lower DLPFC spine density reported in schizophrenia (38, 46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also observed decreases in mitochondrial related genes in pyramidal neurons in the DLPFC of schizophrenia subjects (39, 40). Metabolic systems are strongly linked to the control of synaptic protein connectivity, signaling, and turnover (41-45). Thus, decreases in mitochondrial function coupled with abnormal glucose utilization in neurons could reduce the capacity of pyramidal cells to sustain a normal complement of dendritic spines, contributing to the lower DLPFC spine density reported in schizophrenia (38, 46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2010;2:a001925 contexts during neuronal development, including: axonal pruning (Watts et al 2004); various aspects of axon guidance (Campbell and Holt 2001;DiAntonio et al 2001;Bloom et al 2007;Lewcock et al 2007); synapse formation (DiAntonio et al 2001;Nakata et al 2005); synapse maintenance (DiAntonio et al 2001;Aravamudan and Broadie 2003;Ehlers 2003;Speese et al 2003); and synapse elimination (Ding et al 2007) (reviewed in DiAntonio and Hicke 2004). Acute treatment with the proteosome inhibitor lactacystin blocks axogenesis in dorsal root ganglion cells (Klimaschewski et al 2006).…”
Section: Initiating and Growing An Axonmentioning
confidence: 99%
“…Mutant subunits act in a dominant negative manner to interfere with proteasome function; in multiple previous studies, they have been shown to inhibit UPS-mediated degradation of known proteasome substrates (Schweisguth, 1999;Speese et al, 2003;Neuburger et al, 2006). Transgenic co-expression of both proteasome subunit mutants in the Drosophila eye using the UAS-GAL4 system has a synergistic effect (Belote JM and Fortier, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic co-expression of both proteasome subunit mutants in the Drosophila eye using the UAS-GAL4 system has a synergistic effect (Belote JM and Fortier, 2002). Previously, it was shown in our laboratory that the proteasome is highly localized at the Drosophila NMJ synapse and that presynaptic inhibition of proteasome function rapidly leads to changes in synaptic transmission that are likely mediated through degradation of the synaptic vessel priming protein DUNC-13 Speese et al, 2003). To examine the effect of inhibiting proteasome function specifically in the postsynaptic cell, we crossed the double-mutant UAS-DTS5, DTS7 line with the muscle-specific MHC-GAL4 line to drive expression of the DTS proteasome mutant subunits specifically in muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation